The content foundations of future philologists’ professional training in the usa higher education - Іконнікова, Марина Валеріївна (ScienceRise: Pedagogical Education, 2016)
The content features of philologists’ professional training in the higher educational system of USA are presented in the article. The author considered the views of American scientists on the essence of notion “curriculum”, its types (subject-oriented and profession-oriented). The content of future philologists’ professional training was determined on the base of analysis of academic plans of American universities. The main scientific approaches (criteria, technological, micro-curricular and macro-curricular ones) and principles that the philologists’ professional training is grounded on are considered. Professional competence and its structure is characterized, professional competences that are formed on the base of defined content of training (node, leader, special ones) are analyzed. The system of disciplines coding in American experience is described and basic cycles of disciplines for future philologists are analyzed